2012
DOI: 10.5402/2012/139862
|View full text |Cite
|
Sign up to set email alerts
|

Comparative Effects of Three Iron Chelation Therapies on the Quality of Life of Greek Patients with Homozygous Transfusion-Dependent Beta-Thalassemia

Abstract: This prospective study assessed the quality of life of patients with homozygous transfusion-dependent beta-thalassemia in Greece receiving three different iron chelation treatments. Patients enrolled were receiving one of the following chelation therapies: deferoxamine (n = 21), deferasirox (n = 75), or deferoxamine in combination with deferiprone (n = 39). The three groups were compared in terms of their quality of life, satisfaction and adherence to treatment, control of their health, and self-esteem through… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
20
1
2

Year Published

2013
2013
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 38 publications
(27 citation statements)
references
References 23 publications
4
20
1
2
Order By: Relevance
“…Despite the difference between the present study and other previous studies in questionnaires, methodologies, and number of patients used, our scores of QoL domains in both DFO and DFX groups were comparable to many other studies (19,27,28) and showed severe impairment in all aspects of QoL, table (4). Adult patients using DFX show better QoL than patients' using DFO, and this was consistent with many studies (19,29,30) . Table (5) shows a significant direct relationship between DFX and all QoL domains; this was explained by Goulas et al (30) who reported that patients are more adherent to the oral iron chelator which is considered an important parameter for treatment success.…”
Section: Discussionsupporting
confidence: 89%
“…Despite the difference between the present study and other previous studies in questionnaires, methodologies, and number of patients used, our scores of QoL domains in both DFO and DFX groups were comparable to many other studies (19,27,28) and showed severe impairment in all aspects of QoL, table (4). Adult patients using DFX show better QoL than patients' using DFO, and this was consistent with many studies (19,29,30) . Table (5) shows a significant direct relationship between DFX and all QoL domains; this was explained by Goulas et al (30) who reported that patients are more adherent to the oral iron chelator which is considered an important parameter for treatment success.…”
Section: Discussionsupporting
confidence: 89%
“…As we can see from the final models in the regression analysis, the use of combination chelation therapy (Desferrioxamine & Deferoxamine) had a positive effect in physical fatigue, which means that it correlates with reduced fatigue, while the use of subcutaneous chelation therapy (Desferrioxamine) had a negative effect in general fatigue and was correlated with increased fatigue. Our results supports the findings of other studies that different types of chelation therapy have a significant effect on health self-assessment, with patients receiving oral chelation therapy reporting better HRQoL (Lourenco et al, 2005) and is consistence with other studies that suggests that the quality of life of beta thalassemia major patients is dependent on type of iron chelation treatment which they received (Seyedifar et al, 2016;Karnon et al, 2008;Goulas, Kourakli-Symeonidis, & Camoutsis, 2012). Also, according to previous studies, patients receiving Desferrioxamine were more likely to suffer from fatigue, as well as depression, dyspnea, and decreased physical functioning (Abetz et al, 2006;Pakbaz et al, 2005) Another important factor explaining fatigue, seems to be the qualitative characteristics of fatigue, which was revealed from the opposite correlation, between the variables "existence of fatigue for a period between two weeks and a month" with "existing fatigue before transfusion for less than seven days".…”
Section: )supporting
confidence: 91%
“…49 Of 21 patients receiving deferoxamine and 75 patients receiving deferasirox DT in a second study, only 10% and 33% of patients, respectively, reported that they always adhered to treatment. 48 Among patients with a prior history of iron chelation therapy in the EPIC trial, the proportion of patients with transfusion-dependent thalassaemia who reported always following their iron chelation therapy regimen as recommended by their physician increased from 58 of 179 (32%) patients at baseline to 116 of 173 (67%) patients at end of study (ie, after 1 year's therapy with deferasirox DT or at the time of early discontinuation). 35 In patients with MDS, adherence was reported by 35 of 56 (63%) patients at baseline and 36 of 42 (86%) patients at end of study.…”
Section: Adherence Ratesmentioning
confidence: 99%
“…Patients with transfusiondependent thalassaemia enrolled in a prospective nonrandomised study reported that deferasirox (n = 75) had less negative impact than deferoxamine (n = 21) on HRQoL, the ability to perform daily tasks, and body and skin appearance, which are all factors that may impact adherence. 48 In a multinational study, over 40% of patients receiving deferoxamine infusions (n = 79) reported problems at least sometimes with sticking themselves or with wearing the pump, and patients with poor adherence to deferoxamine also reported issues such as the infusions being painful and the injection site being sore, saturated or leaking. 40 Convenience and administration frequency may affect adherence.…”
Section: Factors Affecting Adherencementioning
confidence: 99%